Adult Ileo-Ileo-Caecal Intussusception: Case Report and Literature Review - Sanjeev Singhal; Anu Singhal; Pankaj K. Arora; Rahul Tugnait; Bishwanath Tiwari; Pawan Malik; Ankur Subhash Dhuria; Vineet Varghese; Mriganka Deuri Bharali; Singh Chandrakant; Pushkar; Vishnu Panwar; et al. (Case Reports in Surgery)
Adult intussusception is a rare entity accounting for only 5% of all intussusceptions and causes approximately 1% of all adult intestinal obstructions. Unlike paediatric intussusceptions which are usually idiopathic, there is usually a lead point pathology which might be malignant in up to 50% cases. We present an unusual case of adult intussusception which was not diagnosed on any investigation including computerized tomographic (CT) scan and magnetic resonance imaging (MRI). It was a case of ileo-ileo-cecal intussusception caused by a large lipoma 38 mm×43 mm×61 mm. It was treated by emergency laparotomy for acute intestinal obstruction. A conservative resection with ileostomy was performed with good postoperative recovery.